2012
DOI: 10.3390/molecules17032367
|View full text |Cite
|
Sign up to set email alerts
|

Beauvericin, a Bioactive Compound Produced by Fungi: A Short Review

Abstract: Beauvericin is a cyclic hexadepsipeptide mycotoxin, which has insecticidal, antimicrobial, antiviral and cytotoxic activities. It is a potential agent for pesticides and medicines. This paper reviews the bioactivity, fermentation and biosynthesis of the fungal product beauvericin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
146
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(169 citation statements)
references
References 44 publications
(74 reference statements)
9
146
1
13
Order By: Relevance
“…The biometabolite beauvericin is first isolated from liquid fermented culture of Beaveria bassiana, which is a common and commercial entomopathogenic mycoinsecticide [6,7]. The genus Beauveria is well known mycoinsecticide and exhibits antimicrobial, antitumor, antifungal and antiviral activities [8]. The entomopathogenic fungus, Beauveria bassiana belongs to Phylum Ascomycota.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The biometabolite beauvericin is first isolated from liquid fermented culture of Beaveria bassiana, which is a common and commercial entomopathogenic mycoinsecticide [6,7]. The genus Beauveria is well known mycoinsecticide and exhibits antimicrobial, antitumor, antifungal and antiviral activities [8]. The entomopathogenic fungus, Beauveria bassiana belongs to Phylum Ascomycota.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that BEA targets the cell organelles such as ribosomes or cell nucleus and enzymes, as BEA is synthesized from amino acids. Unlike other antibiotics example as penicillin which blocks the peptidoglycan biosynthesis of Gram-positive bacteria whose cell wall is not the antibacterial mode of action of beauvericin, although these antibiotics and beauvericin are both from amino acids that are produced by fungi [8]. Bacterial strains which are inhibited by BEA are listed in Table 1.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The cyclodepsipeptides have shown insecticidal activity against several species, such as fifth instar larvae of the silkworm Bombyx mori, 9 Calliphora erythrocephala, Aedes aegypti, Lygus spp., Spodoptera frugiperda, Schizaphis graminum 47 and Sitophilus spp. 48 However, the mycelium and conidia of a B. bassiana strain, pathogenic to Tribolium castaneum and Sitophilus oryzae, showed no toxicity against rats and mice.…”
Section: Larvicidal Activitymentioning
confidence: 99%